Peripheral blood lymphocytes apoptosis role in rheumatoid arthritis progressing - Raisa Aringazina; Nazgul Seitmaganbetova; Aigul Mussina; Yuliya Zame; Samat Saparbayev; Nurgul Zholdassova; Indira Kaibagarova (National Scientific Medical Center, 2023)
Rheumatoid arthritis (RA) is an autoimmune, chronic, and genetically linked inflammatory lesion of joint tissues that is accompanied by extra-articular systemic pathologies. The disease progression leads to joints immobilization, and eventually, the patient's disability occurs approximately ten years from the first clinical manifestation. RA pathogenesis involves various mechanisms: specific joint-related damage, nonspecific adaptive, and vessel-related pathological changes. Our research aimed to study the role of peripheral blood lymphocyte apoptosis in RA pathogenesis. We have analyzed research data from Google Scholar, PubMed, Web of Science, and Scopus databases to investigate the role of lymphocyte apoptosis in RA progression. Clinical manifestations in RA are caused by autoreactive T- and B-lymphocyte activity supported by humoral and cellular immune factors activity. Disease pathogenesis is caused by an imbalance in the process of programmed cell death (apoptosis): a proportion of immune cells are rapidly destroyed. In contrast, apoptosis is inhibited in the other classes of immune cells. High infiltration of the joint by autoreactive sensitized lymphocytes worsens the patient's condition. Apoptosis inhibition is especially noticeable in the early stages of RA and correlates with the concentration of the anti-apoptotic molecule Bcl-2 in the synovia. Activating the apoptotic destruction of lymphocytes (by drug action) allows a positive therapeutic effect and sustained remission. However, it should be noted that genetic factors play a significant role in the onset, progression and drug response of RA. In addition, environmental and behavioral factors can activate RA progression and influence treatment efficacy.